ANALISIS EMPIRIS PENAMPANG GERAM EKUIVALEN PROSES BUBUT ULIR ISO METRIK - Yanis, Muhammad
On turning, machining data information is related to machining data of cylindrical turning. While on the definition of cross-sectional area of the uncut chip, there are differences between cylindrical turning and threading. Methods of definition of chip cross-sectional area of cylindrical turning (expressed on width of cut ,b and undeformed chip thickness,h) cannot be applied directly to threading. Hence on threading it must be approximated to obtain equivalent parameters. Equivalent cross-sectional area (beq and heq) are analyzed from thread profile cutting gradually with equal piece width for every sequence. To find the best methods of approximation have been made, analysis is done on the experiment data of cylindrical turning and threading which are plotted in h (heq) versus ks (specific cutting force) curve. From this analysis, the best equivalent parameters can be obtain which express thread cutting similar to cutting of cylindrical turning.